Effects of Radix Scrophulariae on Hyperthyroidism Assessed by Metabonomics and Network Pharmacology - Zhang, Ning; Lu, Fang; Li, Zihui; Zhao, Hongwei; Pang, Mu; Ye, Tao; Wang, Xijun; Liu, Shumin (Frontiers in Pharmacology, 2021)
Radix Scrophulariae (Chinese name: Xuanshen), a traditional Chinese herb, is used for the treatment of hyperthyroidism, and in this study, its mechanisms were evaluated by metabonomics and system pharmacology. To study the anti-hyperthyroidism effects of R. Scrophulariae, a male SD rat (180-220 g) model of hyperthyroidism induced by Euthyrox was used. Thirty rats were randomly distributed into three groups: the Model group, the R. Scrophulariae treatment group (RS group) and the healthy Control group. Using the UHPLC/Q-TOF-MS metabolomics approach, 44 metabolites were found to be profoundly altered in the model group, and the levels of these biomarkers were significantly decreased after treatment with R. Scrophulariae. Forty-four metabolites and 13 signaling pathways related to R. Scrophulariae, including the biosynthesis of unsaturated fatty acids, primary bile acid biosynthesis and sphingolipid metabolism, were explored, and linoleic acid metabolism and sphingolipid metabolism were identified as the most relevant metabolic pathways. In addition, the system pharmacology paradigm revealed that R. Scrophulariae contains 83 active ingredients and is related to 795 genes, and 804 disease genes are related to hyperthyroidism. The construction of the R. Scrophulariaceae-chemical composition-target-hyperthyroidism network identified a total of 112 intersection genes. The enriched gene targets were analyzed, and five pathways were found to be enriched. Among them pathways, the HIF signaling pathway had the highest enrichment score, which indicated that this pathway might be the main signaling pathway related to the treatment of hyperthyroidism by R. Scrophulariae. The integrated approach involving metabolomics and network pharmacology revealed that R. Scrophulariae might play a role in the treatment of hyperthyroidism by regulating the “IL6-APOA1-cholesterol” pathway and disturbing the HIF signaling pathway. The results demonstrate that the combination of metabolomics and network pharmacology could be used to reflect the effects of R. Scrophulariae on the biological network and metabolic state of hyperthyroidism and to evaluate the drug efficacy of R. Scrophulariaceae and its related mechanisms.